Polysaccharide-fullerene supramolecular hybrids: Synthesis, characterization and antioxidant activity. (15th January 2020) - Kop, Tatjana J.; Jakovljević, Dragica M.; Živković, Ljiljana S.; Žekić, Andrijana; Beškoski, Vladimir P.; Milić, Dragana R.; Gojgić-Cvijović, Gordana D.; Bjelaković, Mira S.
Graphical abstract: Highlights: Polysaccharides (PS) levan and pullulan were hydrophobized by cholesterol. New C60 -PS non-covalent hybrid NPs were synthesized and studied by DLS and SEM. The size of C60 -PS NPs in water was reduced compared to starting PS NPs. DPPH radical scavenging and β-carotene bleaching abilities of NPs were studied. The antioxidant potency increases with the growing hydrophobicity. Abstract: An efficient encapsulation of the fullerene into two hydrophobized and one native polysaccharide provided water soluble supramolecular hybrids. After covalent modification of polysaccharides by cholesterol, noncovalent hybrids were prepared by a three-step procedure, including mixing of individual aqueous solutions of hydrophobized, as well as native sugar with solution of the fullerene in pyridine, dialysis and lyophilization. Although the degree of the fullerene incorporation into hydrophobized substrates, cholesterol-levan and cholesterol-pullulan, was lower in comparison to the native polysaccharide levan, hydrophobization provided nanoparticles with improved properties. The particle size distribution, studied by dynamic light scattering and scanning electron microscopy revealed formation of moderately polydisperse aggregates, with the diameter contraction in comparison to the corresponding free polysaccharide, especially in the case of hydrophobized substrates. The morphological examination, done by scanning electron microscopy indicated the self-organization of the fullerene-native polysaccharide to round individual structures, while fullerene-hydrophobized polysaccharide hybrids tend to form networks. The antioxidant activity of the synthesized polysaccharide-C60 noncovalent hybrids versus starting polysaccharides was investigated by the DPPH radical scavenging and the β-carotene-linoleic acid bleaching methods. In all three complexes, the radical scavenging ability of the fullerene remained preserved, and a positive effect of levan hydrophobization was observed.